Phenomenological analysis of the perception and experience of elementary school teachers' lives of the weaknesses and strengths of the appraisal-descriptive program - . .; . .; . .; . . (پژوهش در نظام‌های آموزشی, 2016)
The purpose of this study was to analyze teachers' perceptions about the weaknesses and strengths of the implementation of the assessment program in elementary schools. It was attempted to use the interpretive approach to redefine the semantic perceptions of teachers about the strengths and weaknesses of the evaluation system, the so-called assessment evaluation, and to show that these participants, both their perceptions and assessments, are well versed in the weaknesses and strengths of the evaluation plan. A qualitative semi-structured interview was used to collect data. Using targeted sampling, data saturation was obtained after conducting 23 interviews with teachers, mostly experienced teachers, with an educational tendency for elementary education. The deep analysis of teachers 'views has led to the identification and categorization of six points of view, such as "reducing the craving, sensitivity and motivation of students' endeavors to learn and study," and "increasing the drop in student learning and education," and the eight strengths of the appraisal program, such as "eliminating The Effort of Teachers to List the Students List "and" The Possibility of Using Multiple Methods in Student Assessment ". The findings showed that the interviewed teachers have experienced different outcomes of the effects of the implementation of the appraisal assessment program.